PENGARUH KONSENTRASI JUS DAUN PEGAGAN DAN PERBANDINGAN CMC DENGAN MAIZENA TERHADAP KARAKTERITIK SORBET - Susilowati, Ida; Ari Sandhi W, Putu; Kartika Pratiwi, I Desak Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2018)
This research was conducted to determine the effect of pegagan juice and the ratio of CMC with maizena to produced the best characteristics of sorbet and to know the concentration of pegagan juice and the ratio of CMC with the right maizena to produced the best characteristics of sorbet. This study used a Completely Randomized Design (CRD) factorial consisting of two factors, the first factor is concentration of pegagan juice as follow 5%, 7,5%, 10% and the second factors is ratio of CMC with maizena as follow 0:1, 0,25:0,72, 0,5:0,5, 0,75:0,25, 1:0. The data obtained were analyzed by analysis of variance and if the treatment have an effect on the parameters observed then continued with Duncan test. The results showed that the best characteristic of sorbet at 10% of pegagan juice concentration and the ratio of CMC with maizena 0.75: 0.25 with the criteria of antioxidant activity 53.50%, Total dissolved solids 210Brix, melting power 61%, green color, sweet taste and a sense of pegagan rather strong and rather soft texture.